Psoriasis, fracture risk and bone mineral density: the HUNT Study, Norway. (15th March 2017) - Modalsli, E.H.; Åsvold, B.O.; Romundstad, P.R.; Langhammer, A.; Hoff, M.; Forsmo, S.; Naldi, L.; Saunes, M.
Summary: Background: An association between psoriasis and osteoporosis has been reported. Objectives: To investigate, in a large prospective population‐based Norwegian study, whether psoriasis is associated with increased risk of forearm or hip fracture; to investigate the cross‐sectional association between psoriasis and bone mineral density (BMD) T‐score in a subpopulation. Methods: Hospital‐derived fracture data from Nord‐Trøndelag County (1995–2013) were linked to psoriasis information, BMD measurements and lifestyle factors from the third survey of the Nord‐Trøndelag Health Study 2006–08 (HUNT3); socioeconomic data from the National Education Database; and use of medication from the Norwegian Prescription Database. Results: Among 48 194 participants in HUNT3, we found no increased risk of forearm or hip fracture in 2804 patients with self‐reported psoriasis [overall age‐ and sex‐adjusted hazard ratio 1·03, 95% confidence interval (CI) 0·82–1·31]. No clear association was found between psoriasis and mean BMD T‐score; overall age‐ and sex‐adjusted differences in total hip, femoral neck and lumbar spine BMD T‐scores were 0·02 (95% CI −0·11 to 0·14), 0·05 (95% CI −0·06 to 0·17) and 0·07 (95% CI −0·09 to 0·24), respectively. No clear association was found between psoriasis and prevalent osteoporosis in either total hip, femoral neck or lumbar spine; overall age‐ and sex‐adjusted odds ratio was 0·77 (95% CI 0·54–1·10). Associations did not change substantially after adjustment for education, smoking, systemic steroid use and body mass index. Conclusions: We found no association between psoriasis and risk of fracture. The study did not indicate reduced BMD T‐score or higher prevalence of osteoporosis among patients with psoriasis. Abstract : What's already known about this topic? An association between psoriasis and osteoporosis has been reported. What does this study add? In this large population‐based prospective study we found no increased risk of fracture among people with psoriasis. In the cross‐sectional analyses, we found no convincing association between psoriasis and bone mineral density or osteoporosis. Respond to this article Linked Comment:Ramot. Br J Dermatol 2017; 176:1117–1118 Plain language summary available online